Drama and AIDS education in Uganda : an interview with Rose Mbowa - Sicherman, Carol; Hutchinson, Yvette; Breitinger, Eckhard (New York : Lehman College, 2000)
This chapter was photocopied from history and theatre in Africa in S outh African theatre journal edited by Yvette Hutchinson and Eckhard Br eitinger
AR/SIC/1/5/9
English
Shelf no. 3
Keywords: Interviews; Education; Literature